Answer:
(2) ![x^2-3x-4=0](https://tex.z-dn.net/?f=x%5E2-3x-4%3D0)
Step-by-step explanation:
Standard form of a quadratic equation: ![ax^2+bx+c=0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0)
When factoring a quadratic (finding the roots) we find two numbers that multiply to
and sum to
, then rewrite
as the sum of these two numbers.
So if the roots <u>sum to 3</u> and <u>multiply to -4</u>, then the two numbers would be 4 and -1.
![\implies b=1+-4=-3](https://tex.z-dn.net/?f=%5Cimplies%20b%3D1%2B-4%3D-3)
![\implies ac=1 \cdot -4](https://tex.z-dn.net/?f=%5Cimplies%20ac%3D1%20%5Ccdot%20-4)
As there the leading coefficient is 1,
.
Therefore, the equation would be: ![x^2-3x-4=0](https://tex.z-dn.net/?f=x%5E2-3x-4%3D0)
<u>Proof</u>
Factor ![x^2-3x-4=0](https://tex.z-dn.net/?f=x%5E2-3x-4%3D0)
Find two numbers that multiply to
and sum to
.
The two numbers that multiply to -4 and sum to -3 are: -4 and 1.
Rewrite
as the sum of these two numbers:
![\implies x^2-4x+x-4=0](https://tex.z-dn.net/?f=%5Cimplies%20x%5E2-4x%2Bx-4%3D0)
Factorize the first two terms and the last two terms separately:
![\implies x(x-4)+1(x-4)=0](https://tex.z-dn.net/?f=%5Cimplies%20x%28x-4%29%2B1%28x-4%29%3D0)
Factor out the common term
:
![\implies (x+1)(x-4)=0](https://tex.z-dn.net/?f=%5Cimplies%20%28x%2B1%29%28x-4%29%3D0)
Therefore, the roots are:
![(x+1)=0 \implies x=-1](https://tex.z-dn.net/?f=%28x%2B1%29%3D0%20%5Cimplies%20x%3D-1)
![(x-4)=0 \implies x=4](https://tex.z-dn.net/?f=%28x-4%29%3D0%20%5Cimplies%20x%3D4)
So the sum of the roots is: -1 + 4 = 3
And the product of the roots is: -1 × 4 = -4
Thereby proving that
has roots whose sum is 3 and whose product is -4.